PERAN PEMERINTAH DALAM PENGELOLAAN PEMAKAMAN PADA MASYARAKAT ETNIS TIONGHOA DI KOTA PADANG - Raju Tamara Dayu; Adil Mubarak (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This research is motivated by problems regarding the management of cemeteries in ethnic Chinese communities in the city of Padang. The amount of funeral levy fees and cremation problems that are not approved by Minang residents. The research aims to determine: (1) The role of the government in the management of cemeteries in the Chinese community in the city of Padang. (2) Government efforts in overcoming the problems that occur due to the management of Chinese community cemeteries in the city of Padang. (3) Obstacles or obstacles in the management of cemeteries in the Tinghoa community in the city of Padang. This type of qualitative research using descriptive methods ,. The selection of informants is carried out using purposive sampling technique. The type of data is primary data and secondary data obtained from interviews with informants and documents related to research. Data obtained through interviews, observation, and study documentation. The research data were analyzed with source triangulation techniques. The findings in the field show that: (1) The role of the government in funeral management in the Chinese community in the city of Padang, namely as a regulator, is a policy maker in improving or optimizing funeral management. As a dynamicator that is able to get the community to participate in overcoming and efficiency and service improvement. As a facilitator, as a provider of burial grounds and facilitating burial grounds. (2) Obstacles or obstacles in the management of cemeteries in the Chinese community in the city of Padang include the lack of available land. The role of the government is still not maximized in managing Chinese ethics public cemeteries. The lack of socialization to the public about the administration and levies of funeral services and the many forms of graves that are not in accordance with applicable regulations. (3) Government efforts in overcoming the problems that occur as a result of the management of Chinese community cemeteries in the city of Padang, among others, determine policies in the field of funeral services in the form of Regional Regulations. Planning spatial planning, development policy is directed at the realization of a synergistic, harmonious and sustainable city spatial plan supported by realistic and implementative spatial planning documents, strict law enforcement, and the availability of responsible implementing agencies. Expansion of land for the tomb area. Openness of data and information presentation by the Funeral UPTD. Matching the size of the meal with the culture of the people of Padang City who have been accommodated in the Regional Regulation become a standard size.